How to analyse ecosystem services in landscapes—A systematic review. (February 2017) - Englund, Oskar; Berndes, Göran; Cederberg, Christel
Highlights: 170 papers reviewed on methods for spatial analysis (mapping) of ES in landscapes. 347 cases of ES mapping described—possible information source for future studies. Large variation in number of mapping cases for different ES. Only twelve percent of all ES mapping cases validated with empirical data. Diverging views on the meaning of landscape in ES literature. Abstract: Ecosystem services (ES) is a significant research topic with diverse modelling and mapping approaches. However, the variety of approaches—along with an inconsistent terminology—cause uncertainties concerning the choice of methods. This paper identifies and qualitatively assesses methods for mapping ES in terrestrial landscapes, based on a systematic review of the scientific literature. It further aims to clarify the associated terminology, in particular the concept of landscape and landscape scale . In total, 347 cases of ES mapping were identified in the reviewed papers. Regulating and maintenance services were most commonly mapped (165), followed by cultural (85), and provisioning services (73). For individual ES, a large variation in number of mapping cases was found. This variation may either reflect the perceived importance of the ES, or that different ES can be more or less easily mapped. Overall, Logical models and Empirical models were most commonly used, followed by Extrapolation, Simulation/Process models, Data integration, and Direct mapping . Only twelve percent of all ES mapping cases were validated with empirical data. The review revealed highly diverging views on the spatial extent of landscapes in studies of ES, and that the term landscape is sometimes used rather arbitrarily.